Genetic variation of gross gill pathology and survival of Atlantic salmon (Salmo salar L.) during natural amoebic gill disease challenge - Richard Taylor; Muller, WJ; Kube, PD; Elliott, NG (2009)
Survival in an experimental disease challenge test or to natural disease challenge is utilised by aquaculture breeding programs as the selection trait for disease resistance. However, these trials are expensive and do not offer the ability to retest animals. The aim of this study was therefore to estimate genetic parameters for resistance to amoebic gill disease (AGD) measured by a categorical scale of gross gill signs (“gill score”) and survival in a field challenge in order to establish whether gill score provides adequate measurement of genetic variation for AGD resistance compared to an AGD challenge survival. A total of 1504 Atlantic salmon smolt, representing 140 full-sib families, was transferred to a marine site in SE Tasmania. The gills were assessed by gill score prior to freshwater bathing on the first two rounds of infection, and then the disease was allowed to develop until mortalities began. Gill score was reassessed after 50 days and mortality was allowed to continue until it had reached a plateau at 100 days. The overall survival rate was 32.3% but varied from 0% to 69% between families. Estimated narrow sense heritability for AGD resistance assessed by gill score varied between 0.23 and 0.48 over the three rounds of infection. Heritability of AGD survival challenge was 0.40 to 0.49 on the observed scale using binary and longitudinal measures. Gill score and survival showed a weak (−0.19) to strong (−0.96) negative genetic correlation which improved when assessed closer to the survival challenge. Estimated genetic gains by selection of the top one hundred estimated breeding values for gill score indicated that up to 82% of the expected gain in survival can be achieved when compared to estimated gain by selection upon survival (days to death), thus minimising selection costs and improving fish welfare whilst allowing repeat measures to be made. The results show that genetic variation of gill score at the early onset of losses closely compares with survival results if the disease is allowed to ...